Effectivity of Project-Based Science Module to Improve Students Critical Thinking Skills on Independent Curriculum for Junior High School Science Learning - Fitriani, Ika Fitriani; Mahardika, I Ketut; Rusdianto, Rusdianto (International Journal of Education, Information Technology, and Others, 2024)
Science education cannot be completed without critical thinking abilities since they enable students to address problems in an efficient and effective manner. Improving these abilities is essential to guaranteeing that students are competent in scientific research. Creating cutting-edge instructional resources is essential to encouraging critical thinking and active student participation. Project-based science modules are particularly notable among these resources because of their capacity to pique interest and promote inquiry. This study employs the ADDIE model as its research framework within the Research and Development (R&D). Pretest and posttest questions, as well as student response surveys, are included in the study instruments. When analyzing data, the N-gain test is employed to assess how well the project-based science module is working. Achieving an N-gain value of 0,53 indicates a notable improvement, categorizing it as moderately successful according to the results. Furthermore, a high satisfaction percentage of 91.33% is revealed by examination of student questionnaire replies, showing a very positive reaction towards the module.